Geometric and dosimetric impact of anatomical changes for MR‐only radiation therapy for the prostate. Issue 4 (1st March 2019) - Nejad‐Davarani, Siamak P.; Sevak, Parag; Moncion, Michael; Garbarino, Kimberly; Weiss, Steffen; Kim, Joshua; Schultz, Lonni; Elshaikh, Mohamed A.; Renisch, Steffen; Glide‐Hurst, Carri
Abstract: Purpose: With the move towards magnetic resonance imaging (MRI) as a primary treatment planning modality option for men with prostate cancer, it becomes critical to quantify the potential uncertainties introduced for MR‐only planning. This work characterized geometric and dosimetric intra‐fractional changes between the prostate, seminal vesicles (SVs), and organs at risk (OARs) in response to bladder filling conditions. Materials and methods: T2‐weighted and mDixon sequences (3–4 time points/subject, at 1, 1.5 and 3.0 T with totally 34 evaluable time points) were acquired in nine subjects using a fixed bladder filling protocol (bladder void, 20 oz water consumed pre‐imaging, 10 oz mid‐session). Using mDixon images, Magnetic Resonance for Calculating Attenuation (MR‐CAT) synthetic computed tomography (CT) images were generated by classifying voxels as muscle, adipose, spongy, and compact bone and by assignment of bulk Hounsfield Unit values. Organs including the prostate, SVs, bladder, and rectum were delineated on the T2 images at each time point by one physician. The displacement of the prostate and SVs was assessed based on the shift of the center of mass of the delineated organs from the reference state (fullest bladder). Changes in dose plans at different bladder states were assessed based on volumetric modulated arc radiotherapy (VMAT) plans generated for the reference state. Results: Bladder volume reduction of 70 ± 14% from the final to initial time point (relative to the final volume) was observed in the subject population. In the empty bladder condition, the dose delivered to 95% of the planning target volume (PTV) (D95%) reduced significantly for all cases (11.53 ± 6.00%) likely due to anterior shifts of prostate/SVs relative to full bladder conditions. D15% to the bladder increased consistently in all subjects (42.27 ± 40.52%). Changes in D15% to the rectum were patient‐specific, ranging from −23.93% to 22.28% (−0.76 ± 15.30%). Conclusions: Variations in the bladder and rectal volume can significantly dislocate the prostate and OARs, which can negatively impact the dose delivered to these organs. This warrants proper preparation of patients during treatment and imaging sessions, especially when imaging required longer scan times such as MR protocols.